PENGEMBANGAN INSTRUMEN ASESMEN KOMPREHENSIF BERBASIS KOMPETENSI PADA MATA PELAJARAN IPA/BIOLOGI - Triyoso, Anang; Ibrahim, Muslimin; Raharjo, Raharjo (JPPS (Jurnal Penelitian Pendidikan Sains), 2013)
This  research  aims  was  to develop  a competency-based  assessment  instruments  in subject  of  Science/Biology.  This research was carried out through the development of the following 4-D design models of Thiagarajan (1974) and then continued the implementation the classroom using One Shot Case Study Design. The data were obtained as follows: the results of the validation instruments decent role in the category; legibility of instruments indicates that the content, appearance, difficulty sentences and interesting pictures and easy to understand students; enforceability of good category; effectiveness of the instrument showed that cognitive assessment to have a reliability tes objective 0.39, the level of difficulty of items were easily as many as 11 items (36.7%), medium as many as 16 items (53.3%), and difficult as many as 3 items (10%), sensitive items as many as 27 items (90%) and less sensitive as many as 3 items (10%), while the essay test has a reliability of 0.45, an easy difficulty level items as many as 2 items (20%), medium as many as 4 items (40%), and difficult as many as 4 items (40%), sensitive items as many as 6 items (60%) and less sensitive as many as 4 items (40%); assessment of the affective domain has a reliability 0.81; assessment of psychomotor domains I has a reliability  of 0.52 and psychomotor  II has a reliability  of 0.62.  Student  field  constraints  are not  accustomed  to using competency-based assessment instrument. Based on the analysis of data, it can be concluded that a Competency-Based Assessment Instruments in subject of Science/Biology that have been developed are valid, practical, and effective.Penelitian  ini  bertujuan  untuk  mengembangkan  instrumen  asesmen  komprehensif  berbasis  kompetensi  pada  mata pelajaran IPA/Biologi. Penelitian ini dilaksanakan melalui pengembangan instrumen mengikuti rancangan 4-D model dari Thiagarajan  (1974)  kemudian  dilanjutkan  implementasi  di  kelas  menggunakan  rancangan  One  Shot  Case  Study.  Data  hasil penelitian yang diperoleh sebagai berikut: hasil validasi instrumen dalam kategori layak; keterbacaan instrumen  menunjukkan bahwa isi, penampilan, kesulitan kalimat dan gambar menarik dan mudah dipahami siswa; keterlaksanaan instrumen berkategori sangat baik; keefektifan instrumen menunjukkan bahwa asesmen ranah kognitif untuk tes objektif memiliki reliabilitas 0,39, tingkat kesukaran butir soal mudah sebanyak 11 butir soal (36,7%), sedang sebanyak 16 butir soal (53,3%), dan sukar sebanyak 3 butir soal (10%), butir soal sensitif sebanyak 27 butir soal (90%) dan kurang sensitif sebanyak 3 butir soal (10%), sedangkan tes uraian memiliki reliabilitas 0,45, tingkat kesukaran butir soal mudah sebanyak 2 butir soal (20%), sedang sebanyak 4 butir soal (40%), dan sukar sebanyak 4 butir soal (40%), butir soal sensitif sebanyak 6 butir soal (60%) dan kurang sensitif sebanyak 4 butir soal (40%); asesmen ranah afektif memiliki reliabilitas 0,81; asesmen ranah psikomotor I memiliki reliabilitas 0,52 dan psikomotor II memiliki reliabilitas  0,62.  Kendala  lapangan  adalah  siswa  belum  terbiasa  menggunakan  instrumen  asesmen  komprehensif  berbasis kompetensi. Berdasarkan hasil analisis data, dapat disimpulkan bahwa instrumen asesmen komprehensif berbasis kompetensi pada mata pelajaran IPA/Biologi yang dikembangkan valid, praktis, dan efektif.